2019
DOI: 10.1186/s40981-019-0267-5
|View full text |Cite
|
Sign up to set email alerts
|

Pectoral nerve II block, transversus thoracic muscle plane block, and dexmedetomidine for breast surgery in a patient with achondroplasia: a case report

Abstract: Background: Patients with achondroplasia have various airway deformations and spinal anatomic abnormalities; therefore, performing general anesthesia and neuraxial anesthesia in such patients can be challenging. Case presentation: A 56-year-old, 112-cm, 30-kg woman was scheduled to undergo partial mastectomy and sentinel lymph node biopsy for cancer of the right breast. She had short limbs, scoliosis, thorax deformation, and chronic moderate to severe mitral regurgitation of the mitral valve. We performed pect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…In addition, intranasal administration of dexmedetomidine has been investigated in studies involving children, which demonstrated that intranasal administration may be a feasible alternative in patients requiring light sedation (21,22); however, more attention should be paid to the differences in dexmedetomidine dosage between children and adults (15)(16)(17)(20)(21)(22). A number of studies have reported the application of intravenous dexmedetomidine in breast lumpectomy (23)(24)(25). Based on the similar efficacy between intravenous and intranasal administration, the present study hypothesized that intranasal dexmedetomidine may be effective in breast lumpectomy procedures.…”
Section: Intranasal Dexmedetomidine Combined With Local Anesthesia Fomentioning
confidence: 99%
“…In addition, intranasal administration of dexmedetomidine has been investigated in studies involving children, which demonstrated that intranasal administration may be a feasible alternative in patients requiring light sedation (21,22); however, more attention should be paid to the differences in dexmedetomidine dosage between children and adults (15)(16)(17)(20)(21)(22). A number of studies have reported the application of intravenous dexmedetomidine in breast lumpectomy (23)(24)(25). Based on the similar efficacy between intravenous and intranasal administration, the present study hypothesized that intranasal dexmedetomidine may be effective in breast lumpectomy procedures.…”
Section: Intranasal Dexmedetomidine Combined With Local Anesthesia Fomentioning
confidence: 99%